Product Development of Cikini Highway Area Reactivation with The Application of Urban Tourism Concept - Athiyyah Izzati Jannah; Sumaryadi (Research and Community Service Center, Politeknik Pariwisata NHI Bandung, 2025)
This study aims to examine the nature and effectiveness of current tourism product development in the Cikini street area, focusing primarily on heritage-based walking tours and assessing how well these tourism products align with established urban tourism product elements and core urban tourism components, identifying strengths, weaknesses, and opportunities to enhance the area's urban tourism appeal and sustainability. Using a descriptive qualitative research design, data were collected through semi-structured interviews with key stakeholders supplemented by literature reviews and field observations. The findings indicate that product development centers on a heritage-themed walking tour highlighting Cikini's historic buildings and their narratives. This aligns with urban tourism's historic district aspect and incorporates primary and secondary product elements. Major strengths include a strong emphasis on Cikini's distinct historical identity, robust government leadership, and infrastructure improvements such as sidewalk renovations and Taman Ismail Marzuki's (TIM) redevelopment. This study also reveals limited community engagement in product development and management and that modern digital and innovative tourism technologies are still in their early phases. This research holds significant theoretical and practical value. Theoretically, it advances the understanding of how urban tourism models and product development frameworks are applied within a Southeast Asian megacity undergoing heritage-led revitalization, emphasizing the need to adapt predominantly Western-origin frameworks to local contexts. It also contributes to discussions on top-down governance in heritage tourism. The study recommends expanding tourism by developing unused waterfront areas, encouraging community co-creation, adopting smart tourism technologies, and strengthening branding and governance to improve Cikini’s socio-economic and cultural impact.